PENGARUH PENERAPAN METODE RESITASI TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 2 LENGAYANG - Dewita, Marta; Zulfaneti, Zulfaneti; Suryani, Mulia (STKIP PGRI Sumbar, 2013)
Studentsâ understanding of mathematis concept in mathematic lesson become the background of this research, many students donât yet real material of the lesson at home and the students are least responsible toword assignment that are gave by the teacher. The purpose of this research is to know: 1) Resitasi method is effective that is used in mathematic lesson, and 2) Studentsâ understanding of mathematic concept at class of XI IPA SMAN 2 Lengayang which use resitasi method is moreÂ good than studentsâ understanding of mathematis concept by using convensional learning. Based Questionnaires that is gave for 26 studentsâ, so it can be seen that resitasi method is verry effective which is used in mathematic lesson, because the analysis of quetionnaires are very effective criteria 77,88%. To see studentsâ understanding of mathematis concept is done hyphotesis test by using uji t one step. In bnefly, it is got hyphotesis are 0,043 with P-value . In summary, Studentsâ understanding of mathematis concept uses resitasi method which is more good than studentsâ understanding of mathematis concept by applying convensional learning.Â Â Â Â Â Â Â Â